1978
DOI: 10.1111/j.1744-6570.1978.tb00455.x
|View full text |Cite
|
Sign up to set email alerts
|

An Extension and Field Test of the Retranslation Method for Developing Rating Scales

Abstract: The retranslation method for rating scale development was used to develop a scale to evaluate an educational television series designed to teach basal reading skills. This extension of the method, outside the context of job performance rating, was evaluated using both developmental and actual field use data. The results during the developmental stage of the method are generally supportive of the use of the technique in this situation; the results from the field test yielded mixed support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Finally, a number of authors have raised questions about the techniques typically used to develop rating scales (Bernardin & Kane, 1980;Dickinson & Tice, 1977;Kane & Bernardin, 1982;Kavanagh & Duffy, 1978;Latham, Saari, & Fay, 1980;Schwab et al, 1975;Shapira & Shirom, 1980). The development of behavior-based rating scales starts with the generation of "critical incidents" of job-relevant behaviors and accomplishments.…”
mentioning
confidence: 99%
“…Finally, a number of authors have raised questions about the techniques typically used to develop rating scales (Bernardin & Kane, 1980;Dickinson & Tice, 1977;Kane & Bernardin, 1982;Kavanagh & Duffy, 1978;Latham, Saari, & Fay, 1980;Schwab et al, 1975;Shapira & Shirom, 1980). The development of behavior-based rating scales starts with the generation of "critical incidents" of job-relevant behaviors and accomplishments.…”
mentioning
confidence: 99%
“…As implied throughout, a performance evaluation system is beneficial if it can contribute to various aspects of organizational functioning in addition to that of performance appraisal. Kavanagh and Duffy (1978) illustrate a "spin-off' use of the retranslation method of scale development for the evaluation of an educational television series designed to teach basic reading skills.…”
Section: A Utilization Criteriamentioning
confidence: 99%
“…Thus, one suggestion is that the final set of BARS be determined after a factor analysis of obtained ratings identifies those items which survive retranslation but yet are still factorially complex; in other words, another stage is added to the development of BARS but this stage is based on preliminary utilization of the scales. Kavanagh and Duffy (1978) did adopt such a strategy and found that factor analysis of field data expanded the number of dimensions in scales which were used to evaluate a television series designed to teach basic reading skills.…”
Section: B Bars Utilization Studiesmentioning
confidence: 99%
“…Alternatively, when resources are scarce and fewer SME groups are available, the same SMEs may be called upon to perform multiple tasks; often this entails the same group of SMEs rating and retranslating critical incidents (Bernardin et al, 1976;Campbell et al, 1973;Hedge et al, 2004;Kavanagh & Duffy, 1978). The retranslation process may also be extremely truncated; in Campion, Pursell, and Brown (1988), an analyst independent of the project reclassified 9% of the critical incidents.…”
Section: Exploring Methods For Developing Barsmentioning
confidence: 99%